2011
DOI: 10.1074/jbc.m110.198655
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Androgen Receptor Activity by HEYL, a Third Member of the Hairy/Enhancer-of-split-related Family of Notch Effectors

Abstract: The Hairy/Enhancer-of-split-related with YRPW-like motif (HEY) family of proteins are transcriptional repressors and downstream effectors of Notch signaling. We previously reported that HEY1 and HEY2 selectively repress androgen receptor (AR) signaling in mammalian cell lines and have shown that in human tissue HEY1 is excluded from the nuclei in prostate cancer but not benign prostatic hyperplasia. We have now characterized a third member of this family, HEYL, which is a more potent repressor of AR activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Therefore, these studies suggested that Notch and AR signaling suppressed each other in prostate cells. However, Belandia et al and Lavery et al also discovered that the interaction between Notch and AR signaling could be disrupted in prostate cancers whereby both Hey1 and HEYL were found to be excluded from the nucleus by unknown mechanisms (Belandia et al 2005;Lavery et al 2011). This disruption was correlated with the malignancy of prostate cancer.…”
Section: Notch and Androgen Receptor In Prostate Cellsmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, these studies suggested that Notch and AR signaling suppressed each other in prostate cells. However, Belandia et al and Lavery et al also discovered that the interaction between Notch and AR signaling could be disrupted in prostate cancers whereby both Hey1 and HEYL were found to be excluded from the nucleus by unknown mechanisms (Belandia et al 2005;Lavery et al 2011). This disruption was correlated with the malignancy of prostate cancer.…”
Section: Notch and Androgen Receptor In Prostate Cellsmentioning
confidence: 94%
“…In addition, HEYL, the third member of Hey family and also an effector of Notch signaling, was found to be a more potent repressor of AR signaling. Similar to Hey1, HEYL bound to AR activation function-1 and blocked AR activity, leading to the suppression of androgen-dependent prostate cancer cell growth (Lavery et al 2011). In contrast, a study also suggested that AR signaling repressed Notch signaling (Nantermet et al 2004).…”
Section: Notch and Androgen Receptor In Prostate Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…5. Studies on prostate tissue and cancer cell lines elucidated a role for the downstream NOTCH transcriptional repressors, HEY1 and HEYL, in the inhibition of AR-mediated gene transcription via interactions with the AF1 region of AR and direct competition with the AR coactivator SRC1 (Belandia et al 2005, Belandia & Parker 2006, Lavery et al 2011. This was proposed as a mechanism by which aberrant prostate growth develops androgen independence.…”
Section: Integration Of Notch and Armentioning
confidence: 99%
“…Heterodimers between Hes1 and Hey factors potentially silence achaete-scute homolog 1, which results in the maintenance of an undifferentiated state of tumors (124)(125)(126). Histone deacetylases (HDAC) are potentially involved in the repressive effects of Hey factors, as treatment with trichostatin A, a pan class I and II HDAC inhibitor, partially abrogates the repressive effect of Hey factors (127)(128)(129). It has been suggested that Hey factors can use their bHLH domain to recruit the mSin3-NCoR-HDAC1 complex or associate with SIRT1, a member of NAD þ -dependent HDACs, and induce transcriptional repression (11,127).…”
Section: Hey Mediates Histone Deacetylasesmentioning
confidence: 99%